Answer:
The answer is that r = 7/6
Step-by-step explanation:
Given point: (7, 5)
Given slope: m = 6
Use the point slope form of the equation:
y - y1 = m(x - x1)
y - 5 = 6(x - 7)
y - 5 = 6x - 7
y = 6x + 2
Now, find r for the point (r, 9) by substitution:
9 = 6x + 2
6x + 2 = 9
6x = 7
x = 7/6
Proof:
y = 6x + 2
f(x) = 6x + 2
f(7/6) = 6(7/6) + 2
= 42/6 + 2
= 7 + 2 = 9, giving (7/6, 9). r = 7/6
Hope this helps! Have a great day!
Answer:
-6 This is your answer it help you
The answer to your question is A. Y= -4x-9 because is you look at the pre written equation it shows that 4x is negative and that 9 is negative too. Also, if you rewrite an equation you have to isolate Y. Therefore A is the correct answer
Answer:
AAS method can be used to prove that the two triangles are congruent.
Step-by-step explanation:
According to the question for the two triangles one pair of opposite angles are equal. One another pair of angles are equal for the two and one pair of sides are also equal of the two.
Hence, the two given triangles are congruent by AAS rule.
Hence, AAS method can be used to prove that the two triangles are congruent.